2015
DOI: 10.1016/j.urolonc.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Is anatomic complexity associated with renal tumor growth kinetics under active surveillance?

Abstract: Introduction Linear growth rate (LGR) is the most commonly employed trigger for definitive intervention in patients with renal masses managed with an initial period of active surveillance (AS). Using our institutional cohort, we explored the association between tumor anatomic complexity at presentation and LGR in patients managed with AS. Methods and Materials Enhancing renal masses managed expectantly for at least 6 months were included for analysis. The association between NS and LGR was assessed using gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Focal ablative therapies such as RFA or cryoablation offer alternative nephron‐sparing options for minimally invasive intervention. Whereas meta‐analysis has shown an increased local recurrence rate after RFA or cryoablation compared with partial nephrectomy , more recent data demonstrated no significant difference in local recurrence rates in a 1424‐patient cohort . Despite the limitation of a small sample size, there was a high rate of persistent viable tumor after initial RFA that required repeated treatment in this review.…”
Section: Discussionmentioning
confidence: 67%
“…Focal ablative therapies such as RFA or cryoablation offer alternative nephron‐sparing options for minimally invasive intervention. Whereas meta‐analysis has shown an increased local recurrence rate after RFA or cryoablation compared with partial nephrectomy , more recent data demonstrated no significant difference in local recurrence rates in a 1424‐patient cohort . Despite the limitation of a small sample size, there was a high rate of persistent viable tumor after initial RFA that required repeated treatment in this review.…”
Section: Discussionmentioning
confidence: 67%
“…15,12,16 However, others have found that growth rate is associated with sizes of renal masses on diagnosis and imaging features assessing tumor complexity. 17,18 The growth rate of renal masses followed on AS can be established from the assessment of serial imaging, which can provide valuable clinical information in a simple and non-invasive manner. Tumors exhibiting growth faster than expected may provide indications for underlying aggressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many treatments for nephrectomy (PN) and radiofrequency ablation (RFA) are widely used in clinical practice [40]. In elderly patients, the treatment of nmRCC carcinoma must consider surgical risk and comorbidity and other competing causes of death, and 20% of renal masses are pathologically diagnosed as benign [41]. Therefore, to avoid complications caused by surgical procedures, active surveillance (AS) has also begun to be used to treat clinical nmRCC.…”
Section: Discussionmentioning
confidence: 99%